Penilaian Tingkat Kesehatan Perbankan Syariah di Indonesia dengan Metode RGEC - Rina Agustina (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
In this research, descriptive method with quantitative approach is used to calculate and describe RGEC method .Sampling technique using Jugement Sampling technique. Results during the period 2013-2015 using RGEC method show that the bank with the healthy predicate in 2013 are BSM, BRI Syariah, BJB Syariah and Bank Victoria Syariah while the predicate is healthy is Bank SyariahBukopin. In 2014, banks with healthy predicate are BSM and BJB Syariah while the predicates are BRI Syariah, Bank SyariahBukopin, and Bank Victoria Syariah. In 2015 banks with a healthy predicate are BSM, BRI Syariah and Bank SyariahBukopin while the predicate is healthy enough BJB Syariah and Bank Victoria Shariah.